Perception of hematologists and oncologists about the biosimilars: A prospective Tunisian study based on a survey. (January 2020) - Hadoussa, Selma; Bouhlel, Mehdi; Soussi, Mohamed A; Drira, Chema; Hadoussa, Myriam; Khrouf, Myriam R
Introduction: Biosimilar drugs have significantly shaken the global pharmaceutical market through a better access to the health care services. The aim of this study is to establish a state of play in Tunisia based on the knowledge and perceptions of doctors on biosimilars in order to identify the problems related to these drugs and to propose solutions for improvement. Materials and methods: In our study, we conducted a prospective, descriptive survey using a questionnaire, destinated to oncologists and hematologists with different grades, from both public and private sectors and from several regions. The questions focused on physicians' general knowledge of biosimilars and their comparison with reference on safety, quality, efficacy, and indication. Finally, we explored the proportion of physicians who are favorable to the policy encouraging biosimilar use. Results: One hundred and seven doctors among 150 answered the questionnaire; 57% were oncologists and 43% were hematologists. About one over five physicians defines biosimilar as a chemical drug. About 29% do not differentiate between a biosimilar and a generic one. A percentage of 68 believe that a biosimilar can have all the indications of its reference following complementary clinical studies. On the other side, 68.2% support the policy encouraging these drugs. Last, only 3.7% of the practitioners believe that they are well informed about biosimilars. Discussion: Our results are comparable to other surveys described in the literature. However, this is the first study that targets oncologists and hematologists specifically. Conclusion: Our study showed a lack of information from oncologists and hematologists about biosimilars in Tunisia. Thus, health authorities should carry out training programs on biosimilars and introduce clear and effective legislation in order to allow better access to health care services.